International trade and social standards - Wilhelm Adamy (Intereconomics, 1994)
The agreements setting up the new World Trade Organisation (WTO) which were signed in Marrakesh have met with widespread approval. The accompanying controversy over the question of social clauses has made the latter an issue of national and international importance which has since been under discussion in many international bodies, such as the International Labour Organisation (ILO), the OECD and the EU. The following two articles present differing views on this issue.
Keywords: 330; Social Clauses